Acceptability of Health Kiosks Within African American Community Settings: A Pilot Study. (16th January 2018) - Abraham, Olufunmilola; Patel, Megha; Feathers, Alison
Introduction: Health kiosks have been increasingly adopted to provide health-care services to those with limited access. Kiosks have the potential to reach people who may have undiagnosed health conditions or those who are not under regular physician care. Thus far, there is limited research assessing the usefulness of health kiosks in the community. This study aimed to explore the acceptability, usability, usefulness, and overall satisfaction of health kiosks in African American majority community settings. Methods: Two health kiosks were placed in predominantly African American low-income areas in an urban city in Western Pennsylvania. After the kiosk interaction, participants 18 years and older were recruited to complete a survey on their overall kiosk use experience. The technology acceptance model was adapted to develop the survey. Survey responses were analyzed using descriptive statistics. Qualitative survey responses were analyzed using content analysis. Results: Seventy-seven percent of the 31 survey respondents were female and 37.8% were ages 60 to 69 years old. Overall, 90% of participants were satisfied with their kiosk experience and 97% found the kiosk useful for health self-management, with 94% stating that they would use the kiosk again. Conclusion: This study showed that health kiosks are accepted among African Americans in community settings such as churches and community centers. Participants found the kiosks easy to use and an overall useful tool to help manage their health. Future studies are needed to provide a better understanding of health kiosk acceptance among minority populations and in community settings.